Extrato etanólico de byrsonima sericea protege células pc12 da toxicidade induzida pela 6-hidroxidopamina (6-ohda) em um modelo in vitro de parkinsonismo experimental - Assis, Albert Layo Costa (2018)
Parkinson's disease is characterized by the progressive loss of dopaminergic neurons in the pars compacta substantia and oxidative stress is one of the main mechanisms that lead to cell death. Previous studies have shown a high antioxidant activity of the leaf extracts of Byrsonima sericea. The aim of the present study was to evaluate the cytoprotective activity of B. sericea leaf extract (EEBS) in a model of cell degeneration induced by 6-OHDA in culture of PC12 cells, an in vitro model of parkinsonism. The quantification of the phenolic compounds of the extract by HPLC-DAD revealed the presence of geraniin, rutin, isoquercetin, Kaempferol-3-O-β-rutinoside and quercetin at concentrations of 8.50; 7.83; 9.08; 29.98, 2.12 mg / g extract respectively. The 75 μg / mL concentration extract protected PC12 cells from the toxicity induced by 6-OHDA (25 μg / mL) in the MTT and LDH viability tests, protected cell membrane integrity assessed by propidium iodide and in the DPPH tests and ABTS the effective concentration (EC50) was 5.06 and 2.80 μg / mL respectively, showing a good antioxidant potential. EEBS was able to decrease 6-OHDA-induced nitrite levels by 50% and decrease GSH depletion, maintaining levels 2-fold higher when compared to 6-OHDA-induced toxicity. EEBS was also able to decrease the number of apoptotic cells from 81.41% to 59.10% in the annexin-V / 7AAD test. In this way, we suggest that the ethanolic extract of B. sericea can be explored as a possible neuroprotective agent for Parkinson's disease due to its high antioxidant capacity and antiapoptotic action.